Thinking the Urban Impasse Beyond Lockdown: An Afterword - Christine Hentschel (Tijdschrift voor economische en sociale geografie, 2024)
How can the lens of the `urban impasse' help us make sense of the relationship between inequality, institutions and contemporary urban life? And how can urban studies benefit from feminist affect theory to explore the theoretical potential of the `urban impasse'? An impasse is a dead end; it connotes an experience of being stuck, lacking orientation or a sense of the future. Still, an impasse also bears transformative potential as a powerful way of halting and denouncing that which does not work or is heading in the wrong direction—as was powerfully brought to stage in cities around the world by climate change, antiracist and women's rights movements in recent years.
Keywords: 330; Impasse; affect theory; collective life; institutions; urban protest; inequality